Developing a Reference Collection for Starch Grain Analysis in Early Neolithic Western Temperate Europe - Cagnato Clarissa (De Gruyter, 2021)
While we know that cereals played an important role in the diet of Linearbandkeramik (LBK) and Blicquy/Villeneuve-Saint-Germain (BVSG) populations in the Paris Basin, many questions remain to be answered as to the real contribution of other plants. To assess this topic, the recovery of other lines of data beyond macrobotanicals is crucial: starch grains have the potential to reveal additional information regarding past plant use. However, in Western Europe, in particular, for the Neolithic period, there is a significant lag in the development of the discipline. We, therefore, present how our current reference collection (composed of nearly 100 taxa spread across 35 families) was established, the reasoning behind our plant selections, and where the material comes from. Overall, our work shows that even though not all the selected plant organs produce diagnostic starch grains, it may be possible to broaden the spectrum of plants likely consumed by Early Neolithic (and beyond) populations in the Paris Basin, in particular concerning the use of wild plants and specific plant parts, especially underground storage organs (tubers, rhizomes, roots, bulbs, etc.). We believe our research will help guide future scholars in the creation of their own starch grain reference collection and to carry out such analyses on archaeological material from this region by consulting our image database. We conclude by providing a brief summary of what the starch grain record in the Paris Basin tells us to date on ancient plant use.